POTENSI LIMBAH JERUK NIPIS FERMENTASI SEBAGAI FEED ADDITIVE UNGGAS: THE POTENTIAL OF FERMENTED LIME WASTE AS A POULTRY FEED ADDITIVE - Shihah, Hanna Dzawish; Sunarti, Dwi; Prasetyo, Aris Budi; Atmaja, Baluh Medyabrata (Tropical Animal Science, 2025)
Fermented lime waste has potential as a feed additive for poultry, but its utilization is hindered by its high pectin fiber content, which can negatively impact poultry performance. This study aimed to evaluate the effect of Aspergillus niger fermentation on pectin fiber content and the pH value of lime waste. The materials used were lime peel flour and a commercial Aspergillus niger mold. The study followed a completely randomized design (CRD) with four levels of A. niger starter: 0%, 1%, 2%, and 3%. Each treatment was replicated five times. The fermentation process was conducted under aerobic conditions for five days at room temperature. The results showed that fermentation with A. niger significantly increased the pH value of the fermented lime peel flour (P < 0.05) and decreased its pectin fiber content (P < 0.05).